Optimization of a novel flat-plate microbial electrolysis cell (MEC) for swine wastes to hydrogen - Ericson, Mason (My University, 2025)
As economic volatility and geopolitical conflict marks the 2020s, vulnerabilities in the global supply chain have highlighted the need for diversification in the sourcing of essential resources. These risks have heightened the need for sustainable resource recovery technologies. Hydrogen is an alternative energy source by itself, while also emerging as a key element in petroleum refining, metal treatment, chemical synthesis, fertilizer production, food processing, and as a fuel additive for biomanufactured aviation fuel. This study evaluated the development and performance of a novel flat-plate microbial electrolysis cell (MEC) designed to produce high-purity hydrogen gas from wastes, specifically swine wastewater, which is generated in large quantities by livestock operations. Initially, acetate was used as a substrate, followed by swine wastewater with a Chemical Oxygen Demand (COD) range of 5,000 to 30,000 mg/L. The MEC featured a shared anode chamber with two carbon fiber anodes (total projected area of 300 cm²) and two flanking cathode chambers with stainless steel mesh cathodes. The anode potential was maintained at -0.3 V versus an Ag/AgCl reference electrode, with continuous monitoring of current density, applied potential, and regular sampling of gas production, pH, COD, and volatile fatty acid (VFA) concentrations. During the acetate trials, the MEC was operated for seven consecutive batch cycles before transitioning to semi-continuous feed conditions. In the batch phase, it achieved a maximum volumetric hydrogen production rate of 0.99 L/Lcathode/d (1.02 mol H₂/mol COD), a peak current density of 8.99 A/m² at an applied voltage of 1.32 V, and a maximum coulombic recovery of 78%. Under continuous operation, these values improved significantly, with a hydrogen production rate of 7.29 L/Lcathode/d (2.56 mol H₂/mol COD), a current density of 7.31 A/m² at 1.18 V, and a coulombic recovery of 111% (coulombic efficiency of 114%). After continuous acetate experiments, the system was switched to swine wastewater for six batch cycles with the incorporation of anaerobic microbial consortia pre-enriched with swine wastewater to maintain an overall solids concentration of ~1% total solids (TS) in the anode suspension. Despite the transition to a more complex substrate and a COD shock of 30,000 mg/L on the fourth batch, the MEC rapidly acclimated and achieved a maximum volumetric hydrogen production rate of 3.56 L/Lcathode/d (0.83 mol H₂/mol COD), a peak current density of 10.32 A/m² at an applied voltage of 1.35 V, and a coulombic efficiency of 86%. Throughout each phase of operation, high purity hydrogen was maintained, with slight decreases during the swine wastewater batch. The volume/volume headspace hydrogen concentrations were 97±6% for batch acetate, 100±2% for continuous operation, and 95±2% for the swine wastewater phase. The current densities reported with swine wastewater in the novel flat-plate MEC are among the highest reported values in published literature and it further demonstrated resilience to variations in influent organic concentrations, yielding current densities substantially higher than those of existing wastewater studies. Hydrogen production and current densities demonstrated by the swine wastewater operation show considerable promise for further exploration in real-world applications while lowering the applied voltage to ~0.5 – 0.8V, for energy positive and economically viable operation at scale.
Keywords: Hydrogen; Microbial electrolysis cell; Acetate; Swine; Wastewater; Cyclic voltammetry